Detection of Some Protozoan Parasites That Infect the Human Gastrointestinal Tract - mmad, T. K. Moha.; I1adbel, A.M.; AI-Raz3q, S. .; Aiaywi, J.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Stool speeimens were collected from pati nts who presented for various medical c:omplaints  in out patien.t Laboratories (The Central Health  Laboratories  /  Baghdad,). Every ,$pecim-en  wa:s  examined  by Conventional   m jcroscopic  exatninatitnl  (CME) Â·and  te.Â§t d,  by  IgGÂ ELISA kit.Antibody against d1e Entamoeba histolylica, det cted  by ELISA, has Â·the potential  to  become a vah,mble adjunct  to blood diagn9stics and make it  more affective, .although there is no repJacement fo'e therp.iorosGopicexamination  because other  potential , pathogens  could otherwise escape detection.Qur .study  was conducted .in AL.., Ya.mtok Hospital  and the CentralHealth  Laboratories  in  Baghdad  to  identify Â· thprevalence  of  E.hi'sa_lytiaa and  Git11â€¢dia  lambl'ia uq_ng  pati nts who attended  these two  clinics  .  General  stool  examination   was -carried  out  for  eacll patient usin,g direct method. The overall rates  of protozoal infections with E.histolytica among all diatTheal cases were 4'0.6% ;. 4-2.5% ;40%;52.8% ; 4T5% ; 49.3 %and 46.1% in years between March  19'99 tq December  2006  respectively  (except  2QOJ), and  for  int c:tion  with: G: lami}lia wer  2 .3% ;20% Â· 15 ,GiJio ;13.6% Â·23% ;17.2%  and 2 .4% in years from  March  1999 to December  200'6 respectivelY {Except2003).The hi_ghest  rate of  infection  \Â¥ith E.  hisroljHica  was  52.!)% in.:2002and for G.lantblitiwas (23.4), % ii1 2:096. The highest rateÂ· of